Overbite correction and sagittal changes: late mixed-dentition treatment effects - Woods Michael (Sciendo, 2001)
This study involved the assessment of preand post-treatment lateral cephalograms from 182 late mixed-dentition patients with Class I and Class II malocclusions, with or without crowding, selected before treatment commenced. It was designed specifically to determine whether antero-posterior mandibular dento-alveolar and skeletal changes occurring with growth and one particular late mixed-dentition treatment approach are influenced in any way by the required amount of incisal overbite correction to be achieved with treatment. Significantly greater forward movements were found at both point B and pogonion in non-headgear patients in whom very deep overbites had been reduced, when compared with patients with less required incisal overbite reduction. This finding would seem to have provided further quantitative evidence to support the concept of unlocking of dento-alveolar structures with early reduction of very deep incisal overbites in appropriate patients. The suggestion was therefore made that the bite-opening in such deep-bite patients should be undertaken at least as early as this late mixed-dentition stage in order to provide an improved environment for the mandibular dento-alveolus as the mandible itself moves forward with normal growth.